(untitled) (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the results of 41 surgically treated radius distal fracture patients. Average follow-up time was 9.8 months (6-19) and mean age was 44.04 (20-81). All patients treated surgically with volar locking plate between the dates October 2010 and November 2018. Material and Methods: There were 11 type A2 (26%), 10 type C2 (24%), 4 type A3 (9%), 3 type B1 (7%), 3 type B3 (8%), 6 type C3 (14%) and 4 type C1 (9%) fractures, respectively according to the AO Classification System. Stewart’s radiological criteria and range of motion were used in clinical and radiological evaluation. QuickDASH-T and Gartland-Werley scores were used for functional assessment.Results: Twenty-three patients (56%) had excellent, 14 patients (34%) had good and 4 patients (9%), respectively had moderate functional scores according to Gartland-Werley scoring scale. Thirty-four patients (83%) were excellent and 7 patients (17%) were good, respectively according to Stewart’s radiological criteria. Average QuickDASH-T score was 5.92 (0-22.7) and average Gartland-Werley score was 3.26 (0-13). Two patients suffered reflex sympathetic dystrophy as a complication.Conclusion: Volar locking plating in distal radius fractures is a reliable treatment method with successful results with careful preoperative planning, attentive surgical approach and systematical rehabilitation. It should be considered as treatment of choice for all but especially active and demanding patients.